The effect of using the cooperative integration strategy (Jigsaw) on the level of skills and self-confidence for the effectiveness of the triple jump - Hamid, Jarwan; Ombarak, Muhammad; Saleh, Behzad (Humanities Journal of University of Zakho, 2022)
This research aims to reveal (the effect of the cooperative integration strategy (Jigsaw) on the skill level of the effectiveness of the triple jump among the students of the second stage in the Department of Physical Education and Sports Sciences, the effect of the strategy of cooperative integration (Jigsaw) on the digital level of the effectiveness of the triple jump among the students of the second stage in the Department Physical Education and Sports Sciences, the effect of the collaborative integration strategy (Jigsaw) on the development of self-confidence among students of the second stage in the Department of Physical Education and Sports Sciences) and the researchers used the experimental approach for its suitability to the nature of the research. Faculty of Education / University of Zakho for the academic year (2021-2022), the number of which is (37) male and female students, divided into two experimental and control groups, where each group consisted of (12) students, after conducting homogeneity and equivalence, applying the experiment and processing the data statistically, the researchers concluded that The following results (the cooperative integration strategy (Jigsaw) contributed in a positive way to the skillful performance and the digital level of the triple jump competition for the members of the experimental group, The traditional method (explanation and model) contributed in a positive way to the skillful performance and the digital level of the triple jump competition for the control group members. ) is greater than the size of the effect of the traditional method, which indicates the preference of the cooperative integration strategy (Jigsaw) used in the triple jump competition. The cooperative integration strategy (Jigsaw) contributed in a positive way to the development of self-confidence for the members of the experimental group. In the development of self-confidence for the members of the control group, there is an effect size of each of the cooperative integration strategy (Jigsaw) and the traditional method on the development of self-confidence, but the size of the effect of the cooperative integration strategy (Jigsaw) is greater than the size of the effect of the traditional method, which indicates the preference of the cooperative integration strategy (Jigsaw). ) used in the development of self-confidence)